Status and influencing factors of dual health literacy in modern medicine and traditional Chinese medicine among Chinese residents - Mi, Fenfang; Zhou, Wenkai; Wang, Lingzhi; Yuan, Fang; Qian, Min; Zhang, Hongxia; Xu, Ningjun (Frontiers in Public Health, 2025)
BackgroundDual Health Literacy (DHL), integrating modern and traditional Chinese medicine (TCM), is crucial for health management in China. However, many struggle with both systems, causing fragmented decisions and poor outcomes. Most studies address only one system, overlooking their interplay. This study bridges the gap by assessing DHL and its key influencing factors to support integrated healthcare.MethodsBased on standardized 2017 questionnaires, this survey assessed health literacy based on modern medicine (HL) and traditional Chinese medicine (TCM-HL) among Chinese residents aged 15 to 69, using sampling via an online Sojump questionnaire. Group differences were assessed using the Mann–Whitney and Kruskal-Wallis test for continuous variables, and the chi-square test for categorical variables. Multivariate logistic regression was employed to identify factors associated with HL, TCM-HL, and DHL.ResultsA total of 605 participants (median age: 23.0 years, IQR: 20–45) were surveyed, with the majority being female (69.4%), rural residents (59.8%), or holding junior college or undergraduate education (68.4%). Standard attainment rates were 27.1% for HL, 10.9% for TCM-HL, and 6.8% for DHL, with a strong correlation between HL and TCM-HL (r = 0.81). The lowest attainment was observed in basic medical literacy (13.2%), health skills (15.0%), chronic disease prevention & control (16%) within HL, and healthy lifestyle (0%) and appropriate methods of public health within TCM-HL (3.5%). DHL was higher in suburban and urban areas than in rural areas (13.3 and 9.4% vs. 4.7%; χ2 = 6.453, p = 0.04). Urban residence (AOR = 1.60, 95% CI: 1.09–2.34, p = 0.016), higher education level (AOR = 1.64, 95% CI: 1.22–2.21, p = 0.001) and health insurance coverage (AOR = 2.74, 95% CI: 1.12–6.68, p = 0.027) were significantly associated with higher HL attainment. Higher education level (AOR = 1.78, 95% CI: 1.33–2.37, p < 0.001) was significantly associated with TCM-HL attainment.ConclusionGiven the strong correlation between HL and TCM-HL, promoting the integrated concept of DHL is essential. The low DHL level underscores the need for targeted support, particularly for rural, less educated and uninsured residents. Efforts should enhance both modern and TCM health strategies, emphasizing health skills, chronic disease prevention and basic medical literacy in HL and healthy lifestyle and appropriate public health approaches in TCM-HL.